Double-Edged Sword: AI Tools Dependency and Empowerment among Office Administration Students: A Case Study of Bachelor of Science in Office Administration of Camarines Sur Polytechnic Colleges, Philippines - Francia, Jasmine A.; Relos, Danica Joy R.; Bandiola, Gladwyn Christian T. (Bincang Sains dan Teknologi, 2025)
This study aims to investigate the dual nature of Artificial Intelligence (AI) tools such as ChatGPT as a double-edged sword. The respondents of this study are Two Hundred Fifteen (215) Office Administration students. Purposive sampling was utilized to identify the participants in this study, including those Office Administration students who are familiar with the use of ChatGPT. This study used a descriptive correlational research design that utilizes a checklist questionnaire for gathering data. For statistical tools, the percentage technique, slovin’s formula, Likert scale, weighted mean, and rank order method were used. The findings revealed that Office Administration students “Sometimes” use AI tools such as ChatGPT in terms of both extent and duration. For the effects contributing to respondents' AI tools dependency, the results revealed respondents “Disagree” with positive effects and “Agree” with negative effects in terms of accessibility. In terms of efficiency, the respondents are “Agree” in both positive and negative effects. The indicators listed under educational pressure, the respondents “Agree” with positive effects and “Disagree” with the negative effects. Lastly, when it comes to work ethics, the respondents revealed that they “Agree” with the positive effects and “Disagree” with the negative effects. As an output, the researchers proposed an action plan to mitigate the perceived dependency while also empowering the respondents. This action plan is designed and aligned based on the results of the survey.